Long-term results of electrical stimulation of the lower esophageal sphincter for the treatment of gastroesophageal reflux disease - Rodríguez, L.; Rodriguez, P.; Gómez, B.; Ayala, J. C.; Oksenberg, D.; Perez-Castilla, A.; Netto, M. G.; Soffer, E.; Crowell, M. D. (Endoscopy, 2013)
Background and study aims: In patients with gastroesophageal reflux disease (GERD), temporary electrical stimulation of the lower esophageal sphincter (LES) increases LES pressure without interference with LES relaxation. The aim of the current study was to investigate the safety and efficacy of long term LES electrical stimulation therapy (LES–EST), using a permanently implanted stimulator for the treatment of GERD.Patients and methods: Patients with GERD who were at least partially responsive to proton pump inhibitors (PPIs) and who had hiatal hernia of ≤ 3 cm and esophagitis of Los Angeles Grade A, B, or C were included in the study. Stimulation electrodes were placed in the LES and a pulse generator (EndoStim LES Stimulation System; EndoStim BV, The Hague, The Netherlands) was implanted laparoscopically. LES stimulation was delivered at 20 Hz, 215 μs, 3 – 8 mA in multiple 30-minute sessions. Patients were evaluated at follow-up using the GERD Health-Related Quality of Life (HRQL) questionnaire, daily symptom and medication diaries, the SF-12 Health Survey, esophageal pH testing, and high resolution manometry.Results: A total of 24 patients (mean age 53 ± 12 years; 14 men) were implanted and 23 completed the 12-month evaluation. No serious implantation or stimulation-related adverse affects or sensations were reported. Median composite GERD–HRQL score at 12 months was 2.0 (interquartile range [IQR] 0 – 3.0), which was significantly better than baseline scores both on PPI therapy (median 9.0, IQR 6.0 – 10.0; P = 0.002) and off PPIs (median 23.5, IQR 21 – 25.75; P < 0.001). The median percentage of the 24-hour period with esophageal pH < 4.0 at baseline was 10.1 % (IQR 7.7 – 15.5), which was reduced to 3.3 % (1.8 – 6.9) at 12 months (P < 0.001), with 69 % of patients showing either normalization or > 50 % improvement in their distal esophageal pH. At 12 months, 96 % of patients (22/23) were completely off PPI medication.Conclusion: During the long term follow-up of 12 months, LES – EST was safe and effective for the treatment of GERD. There was a significant and sustained improvement in GERD symptoms, reduction in esophageal acid exposure with elimination of daily PPI usage, and no stimulation-related adverse effects.